Long COVID: Costs for the German economy and health care and pension system - Afschin Gandjour (BMC, 2023)
Abstract Background Patients with acute COVID-19 can develop persistent symptoms (long/post COVID-19 syndrome). This study aimed to project the economic, health care, and pension costs due to long/post-COVID-19 syndrome with new onset in Germany in 2021. Methods Using secondary data, economic costs were calculated based on wage rates and the loss of gross value-added. Pension payments were determined based on the incidence, duration, and amount of disability pensions. Health care expenditure was calculated based on rehabilitation expenses. Results The analysis estimated a production loss of 3.4 billion euros. The gross value-added loss was calculated to be 5.7 billion euros. The estimated financial burden on the health care and pension systems due to SARS-CoV-2 infection was approximately 1.7 billion euros. Approximately 0.4 percent of employees are projected to be wholly or partially withdrawn from the labor market in the medium term due to long/post-COVID with new onset in 2021. Conclusion Costs of long/post-COVID-19 syndrome with new onset in 2021 are not negligible for the German economy and health care and pension systems but may still be manageable.